URGENSI PEMAHAMAN MAKANAN HALAL DAN BAIK PADA MASYARAKAT LAU GUMBA KECAMATAN BERASTAGI - Tambunan, Nurhalima (Jurnal Ilmiah Al-Hadi, 2018)
This research was conducted to know the understanding of the Lau Gumba community on halal and good food. The object of the study was a study group of mothers in Lau Gumba Village, Berastagi, Karo. The application of halal is very useful because it will be applied in family life. This research is expected to provide a solution in striving for Muslims who are in Lau Gumba Village to maintain and consume halal and good foods where human nature is greatly influenced by what they eat. This research was conducted for 9 months, in order to obtain data and information researchers used a qualitative approach by observations and interviews. This research is very useful for the benefit of the people, nation and state in realizing the ideals of the struggle of the Republic of Indonesia, where the preservation of Muslims from halal and haram will manifest a freedom and satisfaction with the implementation of each worship.